Electronic Word of Mouth as a Moderating Variable of the Influence of User-Generated Content on Purchasing Decisions - Harjanto Suwardono (Yayasan Inovasi Kemajuan Intelektual, 2025)
This research is a quantitative study with an approach, namely the approach of several previous studies, as the main fuel to grow or create a hypothesis similar to prior research, modify it by adding several new variations, and prove it. The data that the researcher uses in this study is primary data that the researcher obtained from two hundred and fifty-five Eiger Customers in Indonesia who purchased goods through user-generated content intermediaries. The data used in this study is primary data that the researcher analysed using the smart PLS 4.0 analysis tool. The result in this article shows that the two hypotheses used in this study can be accepted and proven. In the first hypothesis, the User Generated Content variable is stated to have a positive relationship direction and a significant influence on Purchasing Decisions. This is because the ​​P-value is positive and is below the significance level of 0.05, namely 0.016. These results are in line with previous studies that have been mentioned above. These results indicate that user-generated content can widen the market, make marketing more attractive, and ultimately influence purchasing decisions. In the next hypothesis, the Electronic-Word of Mouth variable can also moderate the influence of the User Generated Content variable on Purchasing Decisions. This is because the same thing is that the ​​P-value is positive and below the significance tariff of 0.000. These results show that the Electronic Word Of Mouth variable can make attractive marketing even more attractive, so that after moderation, its influence is more substantial than before, 0.016